The home advantage in individual sports: An augmented review - Jones, M. B. (Psychology of Sport and Exercise, 2013)
Objectives: Is the home advantage in individual sports comparable in magnitude and consistency to that in team sports? If not, is it nevertheless a major factor? The present paper reviews the literature to date with respect to these questions and augments it with original analyses where appropriate. Design: The review is framed and dominated by a design consideration, namely, that all major team sports play balanced home-and-away schedules, whereas individual sports rarely, if ever, do. As a result, it is necessary to take player quality into account in assessing home advantage in an individual sport. Method/approach: The paper begins with three individual sports (tennis, golf, and boxing) in which home advantage has been studied using available controls for player quality. It moves on to individual and team sports in the Olympics, where home advantage has also been studied with credible controls on player (country) quality. Studies are then reviewed in which player quality has not been controlled. Finally, data are presented for two individual efforts embedded in team sports (free throws in basketball and shootouts in ice hockey). Results: Subjectively evaluated sports such as diving, gymnastics, or figure skating usually show sizable and significant home advantages. Otherwise, occasional findings have been reported but they are not consistent within a sport, are generally weak, and often statistically unreliable. Conclusions: Except for subjectively evaluated sports, home advantage is not a major factor in individual sports, much less does it play a role in individual sports comparable to its role in team sports.